Terminal value calculation in dcf valuation models: An empirical verification - Adam Behr; Paweł Mielcarz; Dmytro Osiichuk (e-Finanse: Financial Internet Quarterly, 2018)
The paper presents an empirical verification of the main assumptions underlying the calculation of terminal value in DCF valuation models. The test results suggest that the volatility of free cash flows and the dynamism of the operating environment do not allow us to make a reliable long-term forecast of value creation potential of the public companies in Poland. Regardless of their organic growth phase, the overwhelming majority of the sampled firms are evidenced to exhibit extreme year-on-year fluctuations of sales, investments and cash flows over the short- and medium-term observation windows. The variability of operating results and the probabilistic nature of company-level fundamentals may preclude the possibility of constructing a reliable cash flow forecast for the purposes of a DCF valuation. This methodological issue appears to pose a particular challenge during the calculation of terminal value, which is heavily dependent on highly subjective and uncertain steady-state fundamentals.
Keywords: G17; G32; G38; 330; DCF valuation; terminal value; intrinsic value